Is Sperm Freezability Related to the Post-Thaw Lipid Peroxidation and the Formation of Reactive Oxygen Species in Boars? - Gómez-Fernández, José; Gómez-Izquierdo, Emilio; Tomás, Cristina; Mocé, Eva; De-Mercado, Eduardo (Blackwell Publishing Ltd, 2017)
The aim of the present study was to determine whether the levels of reactive oxygen species (ROS) substances production and the levels of lipid peroxidation of the sperm membrane were related to the quality that the ejaculates exhibited after cryopreservation in boars. Ejaculates from 42 healthy boars were used in this study and they were cryopreserved with the lactose-egg yolk extender (LEY). Several sperm quality parameters were assessed by flow cytometry in samples incubated for 30 and 150 min at 37°C after thawing: the percentage of sperm with intact plasma membrane (SIPM), intracellular reactive oxygen substances production through mean of DCF fluorescence intensity of total sperm (mean-DCF) and the percentage of viable and non-viable sperm containing oxidized BODIPY (VSOB and NVSOB). In addition, the percentages of total motile (TMS) and progressively motile sperm (PMS) were assessed at the same incubation times with a computer-assisted sperm analysis system. The classification of the ejaculates into good or bad freezers was performed through hierarchical cluster analysis from SIPM and TMS at 150 min post-thawing. The ejaculates of those males classified as good freezers exhibited higher (p 0.05) VSOB, NVSOB and mean-DCF. Therefore, these results show that lipid peroxidation and the amount of reactive oxygen substances in the sperm after cryopreservation are similar between boars classified as good or bad freezers.